Meta-analysis on efficacy and safety of new oral anticoagulants for venous thromboembolism prophylaxis in overweight and obese postarthroplasty patients. Issue 6 (September 2015) - Pathak, Ranjan; Karmacharya, Paras; Giri, Smith; Poudel, Dilli Ram; Aryal, Madan Raj; Bhatt, Vijaya Raj; Shamoun, Fadi E.; Pandit, Anil
Abstract : Obesity is an independent risk factor for venous thromboembolism (VTE), and the risk rises further in the postarthroplasty period. Although medication doses often require adjustment for the altered pharmacokinetic profile in obese patients, the efficacy and safety of a fixed-dose regimen of new oral anticoagulants (NOACs) in overweight and obese patients remain unclear. Relevant studies were identified through searches of major databases. Phase III randomized controlled trials that compared NOACs against low-molecular-weight heparin (LMWH) in the prevention of VTE in postarthroplasty patients were included. Efficacy and safety outcomes with NOACs in overweight (BMI 25–29 kg/m 2 ) and obese (BMI ≥ 30 kg/m 2 ) patients were assessed. In five trials involving 16 674 patients, NOACs were found similar to LMWH in preventing VTE and VTE-related deaths after arthroplasty in both overweight and obese patients [odds ratio (OR) 0.64, P  = 0.19 and OR 0.76, P  = 0.43, respectively]. Similarly, the risk of major or clinically relevant bleeding was similar to LMWH in overweight patient with a trend toward lower bleeding in obese patients (OR 0.83, P  = 0.54 and OR 0.44, P  = 0.07 respectively). Apixaban was found to be more effective than LMWH in obese patients (OR 0.54, P  = 0.01) with the lower dose of dabigatran (150 mg) being less effective (OR 1.81, P  = 0.02). Our study suggests that a fixed-dose regimen of dabigatran might be ineffective in severe obesity. However, apixaban at the currently recommended dose seems to be superior to LMWH in obese patients with noninferior bleeding risk. Abstract : Supplemental Digital Content is available in the text